2022
DOI: 10.1002/ange.202114482
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Chemoselectivity of Catalytic Hydroboration with Light

Abstract: The ability to selectively react one functional group in the presence of another underpins efficient reaction sequences. Despite many designer catalytic systems being reported for hydroboration reactions, which allow introduction of a functional handle for cross-coupling or act as mild method for reducing polar functionality, these platforms rarely deal with more complex systems where multiple potentially reactive sites exist. Here we demonstrate, for the first time, the ability to use light to distinguish bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
3
5
0
Order By: Relevance
“…However, it is notable that most approaches to increase reactivity, for instance with amides, do not do so selectively making them unsuitable for complex substrates [17–19] . In this context, we recently reported a unique cobalt catalysed platform whereby the chemoselectivity of ketoacid hydroboration could be controlled by visible light [20, 21] . In line with our previous work, [22] we suggested that the reactivity observed with carboxylic acid hydroboration was consistent with a Co 0 /Co I catalytic cycle [23] …”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…However, it is notable that most approaches to increase reactivity, for instance with amides, do not do so selectively making them unsuitable for complex substrates [17–19] . In this context, we recently reported a unique cobalt catalysed platform whereby the chemoselectivity of ketoacid hydroboration could be controlled by visible light [20, 21] . In line with our previous work, [22] we suggested that the reactivity observed with carboxylic acid hydroboration was consistent with a Co 0 /Co I catalytic cycle [23] …”
Section: Methodssupporting
confidence: 78%
“…[17][18][19] In this context, we recently reported a unique cobalt catalysed platform whereby the chemoselectivity of ketoacid hydroboration could be controlled by visible light. [20,21] In line with our previous work, [22] we suggested that the reactivity observed with carboxylic acid hydroboration was consistent with a Co 0 /Co I catalytic cycle. [23] Upon further mechanistic probes of this carboxylic acid selective hydroboration with in situ NMR (see Supporting Information for more details), we noted key features in the 11 B NMR.…”
supporting
confidence: 89%
“…[ 17 , 18 , 19 ] In this context, we recently reported a unique cobalt catalysed platform whereby the chemoselectivity of ketoacid hydroboration could be controlled by visible light. [ 20 , 21 ] In line with our previous work, [22] we suggested that the reactivity observed with carboxylic acid hydroboration was consistent with a Co 0 /Co I catalytic cycle. [23] …”
supporting
confidence: 88%
“…When more diluted conditions were applied (Table 1 , entry 6), only starting material was recovered, demonstrating the importance of highly concentrated solution for the reaction to occur. Finally, in the absence of the catalyst and any promoter (Table 1 , entry 7), [20] poor selectivity is observed, with all products obtained in similar proportions. The stability of all reagents, ease of reaction set‐up and exquisite selectivity encouraged us to investigate further the reaction scope of this hydroboration protocol (Scheme 2 ).…”
mentioning
confidence: 99%
“…In many cases for the hydroboration of carbonyls, the catalyst functions mainly as a Lewis acid, activating the carbonyl carbon for nucleophilic attack by the hydride of the borane reagent. A number of different transition metals have been used to catalyse this reaction, 430 including rhodium, 424,431 titanium, 401,402,[432][433][434][435][436][437][438] hafnium, 403 molybdenum, 325 silver, 406 cobalt, 169,[439][440][441][442] ruthenium, 404 palladium, 414,443 zinc, 412,413,444-450 iron, 415,[418][419][420]439,440,451,452 nickel, 409,410 manganese, 408,440,453 copper, 421,422 and yttrium. 454,455 Chiral diols combined with titanium(IV) complexes provide up to 99 : 1 enantiomeric ratios in the hydroboration of simple ketones with catecholborane.…”
Section: Ketonesmentioning
confidence: 99%